Simplified Transit Procedure in Railway Transport - Kokorović, Željko; Blašković-Zavada, Jasna; Radoš, Božica (Promet - Traffic&Transportation, 2008)
The current transit procedure in railway transport that iscarried out on the basis of the Customs Act [ 11 of the Republicof Croatia is applied only up to the border, i. e. the issued documentsand guarantees are valid only up to the border, and byjoining the Convention on Common transit procedure, i. e. integrationof the Republic of Croatia in the European Union, theRepublic of Croatia will also have to implement the regulationsand rules of Simplified transit procedure valid in each of thethirty member states. In international railway traffic, the transportof goods is regulated by the Convention concerning InternationalCarriage by Rail- COT IF [2 1 and usage of the CIMwaybill (Contract for International Carriage of Goods by Rail).If the goods are transported in Simplified transit procedure, theformalities regarding the transport of goods performed by railcarriers using the international waybill CIM will be significantlysimplified and accelerated. In principle there are no delays dueto customs on the borders when crossing the EU borders andborders of the Convention member states, contributing greatlyto the acceleration of the transport of goods, reduction of waitingcosts and paperwork, as well as influence on the schedulereliability.